2021
DOI: 10.29408/ab.v2i2.4210
|View full text |Cite
|
Sign up to set email alerts
|

Pelatihan pemanfaatan teknologi sebagai media pendukung pembelajaran untuk guru di Kecamatan Sembalun

Abstract: The involvement of lecturers, students, and teaching staff is an integral form of the Tri Dharma of higher education. Education has a crucial role and is the primary key to producing quality human resources. In the current practice of teaching and learning activities, many teachers have not used media or technology in teaching. Therefore, it is necessary to increase teacher competence through Community Service Activities to adapt to the industrial era 4.0, which is more likely to use technology in various fiel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 4 publications
0
2
0
2
Order By: Relevance
“…Harapannya setiap anggota NA nantinya dapat belajar secara mandiri di rumah apabila saat pelatihan bersama secara langsung belum selesai. Di samping itu dengan melakukan pelatihan akan teknologi tentunya dapat meningkatkan kompetensi TIK (Permana et al, 2021) dan kemampuan pedagogik peserta (Myori et al, 2019).…”
Section: Pendahuluanunclassified
See 1 more Smart Citation
“…Harapannya setiap anggota NA nantinya dapat belajar secara mandiri di rumah apabila saat pelatihan bersama secara langsung belum selesai. Di samping itu dengan melakukan pelatihan akan teknologi tentunya dapat meningkatkan kompetensi TIK (Permana et al, 2021) dan kemampuan pedagogik peserta (Myori et al, 2019).…”
Section: Pendahuluanunclassified
“…Penggunaan teknologi seharusnya bisa menjadi jembatan yang tepat untuk mendorong dalam aktualisasi dari pencapaian tujuan. Seperti kegiatan pengabdian masyarakat yang juga pernah dilakukan oleh (Permana et al, 2021) menjelaskan bahwa dengan mengadakan pelatihan teknologi dapat meningkatkan kompetensi peserta akan teknologi tersebut. Selain itu menurut (Indriyanto et al, 2019) berdasarkan hasil pengabdian masyarakatnya menjelaskan bahwa pelatihan penggunaan aplikasi berbasis android dapat menjadikan para peserta pelatihan menjadi lebih baik dari sisi penggunaannya.…”
Section: Pembahasanunclassified
“…In the process of online learning, several obstacles have been encountered such as the instability of the internet network, limitations of facilities such as smartphones, limitations of the abilities of teachers and students in utilizing technology, and others (Paristiowati et al, 2022). In addition, several teachers have also been found who have not used media in learning activities (Permana et al, 2021). Meanwhile, from field analysis that has been carried out, especially at SMK Yasiha Gubug, it was found that many teachers at the school: 1) have a lack of mastery of information technology as an online learning medium.…”
Section: Introductionmentioning
confidence: 99%
“…The main objective is to provide students with firsthand experience of the process to be capable of resolving issues. Furthermore, Permana et al (2021) Irfani (2015) stated that training in using any type of ERP software is crucial for companies, especially to make users feel comfortable and ready to use the implemented software. The three aspects to be considered when designing training are the logic and concepts of ERP, the features and systems of ERP, and the functional aspects of training.…”
Section: Introductionmentioning
confidence: 99%